Principles in the organization of care to premature infants in the postneonatal period - E. S. Sakharova (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
Based on the analysis of its 15-year activities, the Center for Development Correction in Premature Infants has developed and laid down principles in the organization of a follow-up, treatment, and habilitation of premature infants in the postnatal period. The authors discuss a physician’s required qualification and professional skills and needs for specialists and laboratory studies. They present a scheme for following up a premature baby during 3 years of life and methods for evaluating the psychomotor development and health of a premature baby with consideration with his/her adjusted age.